The Influence of AI (Artificial Intelligence) Animation Videos in Health Promotion on the Implementation of Personal Hygiene Among Elementary School Children at SD Kartika II-6, Bandar Lampung City in 2024 - Parasetyawati, Dhea; Maritasari, Dwi Yulia; Noviansyah, Noviansyah (Universitas Ibn Khaldun Bogor, 2025)
Personal hygiene refers to cleanliness practices undertaken to maintain both physical and mental health. Poor personal hygiene can increase the risk of diseases related to healthy behaviors and personal hygiene habits. A preliminary survey conducted on school-aged children at SD Kartika II-6 in Bandar Lampung City found that 60% of the students exhibited poor personal hygiene practices. The use of AI (Artificial Intelligence) animated video media in health promotion efforts can help deliver information in a more engaging and easily understandable way for school-aged children. This study aims to determine the impact of health promotion using AI-animated video media on the application of personal hygiene among elementary school students. The research employed a quasi-experimental design with a one-group pre-test post-test with control group. The research sample consisted of 18 students in the intervention group and 18 students in the control group, selected using the total sampling technique. The research instruments included a questionnaire and a checklist. The statistical tests used for data analysis were the Paired Sample T-test and Independent Sample T-test. The results indicated a difference in the mean score of personal hygiene practices, which increased from 11.22 ± 3.209 to 13.61 ± 3.460 after the intervention using AI-animated video media. This study demonstrates a significant effect of AI-animated video media on personal hygiene practices (p=0.001) among school-aged children. It is recommended that health promotion using AI-animated video media become a routine activity organized by schools in collaboration with local health centers and parents to improve personal hygiene practices and maintain cleanliness and health in school-aged children.